Lithiumeter: Version 2.0. (December 2016) - Malhi, Gin S.; Gershon, Samuel; Outhred, Tim
Abstract : Background: The Lithiumeter was developed as a visual and practical guide for determining lithium levels in the management of bipolar disorder (BD). It appears to have been well received, as evidenced by its increasing popularity amongst doctors as a deskside clinical aide, and adoption and reproduction of the schematic in clinical guidelines and texts. However, since its publication 5 years ago, key basic neuroscience and clinical research developments pertaining to lithium have significantly advanced our understanding, necessitating further refinement of guidance concerning the practicalities of lithium therapy. Methods: Literature concerning the indications for, and therapeutic levels of, lithium and the associated acute and chronic risks of therapy was scrutinized as part of updating clinical practice guidelines. We have reviewed these updates and identified significant areas of change with respect to the previous Lithiumeter (version 1.0). Results: Since 2011, updated clinical practice guidelines have narrowed the indicated plasma lithium concentration for maintenance therapy, suggesting that additional guidance is necessary for optimizing treatment. Relevant updated clinical guidance was integrated to constitute the Lithiumeter 2.0, which provides a more comprehensive overview of the practical aspects of lithium therapy while maintaining a focus on optimization of lithium levels, such as differential titration of lithium depending on the current mood state. Conclusions: The Lithiumeter 2.0 is an update that clinicians will find useful for their practice. By addressing some of the issues faced in clinical practice, translational clinical research will continue to inform the Lithiumeter in future updates.